242+b2=252

Raise 24 to the power of 2.

576+b2=252

Raise 25 to the power of 2.

576+b2=625

Subtract 576 from both sides of the equation.

b2=625-576

Subtract 576 from 625.

b2=49

b2=49

Take the square root of both sides of the equation to eliminate the exponent on the left side.

b=±49

Simplify the right side of the equation.

Rewrite 49 as 72.

b=±72

Pull terms out from under the radical, assuming positive real numbers.

b=±7

b=±7

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

b=7

Next, use the negative value of the ± to find the second solution.

b=-7

The complete solution is the result of both the positive and negative portions of the solution.

b=7,-7

b=7,-7

b=7,-7

Solve using the Square Root Property 24^2+b^2=25^2